Toxicity of lead poisoning - Oyebamiji, Oyesiji Rilwan; Kezeli, Tamar; Sulashvili, Nodar (Caucasus Journal of Health Sciences and Public Health, 2018)
In ancient time there has been recognition of toxicity of lead among people. Today, lead and its compounds are some of the most well‐studied environmental toxicants. There are Common toxic agents that have been a major concern they are heavy metals, organophosphates, bacterial, and animal neurotoxins are all toxic substances invading the human body. Generally, lead exposure is one of the most frequent and dangerous exposures that can escalate to significant neuropsychological and functional decline in the human body. Lead toxicity is a serious environmental disease and its effects on the human body are disastrous. All functions in the human body are affected by lead toxicity. In countries like US and Canada the use of lead has been controlled extensively, it is still used in large scale by developing countries. This is primarily because it has physical and chemical properties that make it suitable for a large number of applications for which humans have benefitted from. For many years lead has been a major environmental pollutant. Lead is highly persistent in the environment and because of its application in all most, all human produce its levels rise generally in almost every country causing a serious threat.